2016
DOI: 10.1016/j.pedneo.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Endoscopic Reflux Esophagitis and Combined Multichannel Intraluminal Impedance-pH Monitoring in Children

Abstract: MII-pH monitoring not only raised the diagnostic yield in identifying GER, but it also showed significant correlation with the presence of endoscopically proven reflux esophagitis in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 22 publications
1
17
1
Order By: Relevance
“…The six impedance segments defined the six zones along the esophagus, Z1 to Z6, which were centered at 17, 15, 9, 7, 5, and 3 cm above the lower esophagus sphincter, respectively, with Z1 being most proximal to the upper incisor. The three pH electrodes were located in the stomach, 5 cm above the lower esophageal sphincter and 21 cm above the lower esophageal sphincter . All of the segments and electrodes were assumed to locate in the esophagus.…”
Section: Methodsmentioning
confidence: 99%
“…The six impedance segments defined the six zones along the esophagus, Z1 to Z6, which were centered at 17, 15, 9, 7, 5, and 3 cm above the lower esophagus sphincter, respectively, with Z1 being most proximal to the upper incisor. The three pH electrodes were located in the stomach, 5 cm above the lower esophageal sphincter and 21 cm above the lower esophageal sphincter . All of the segments and electrodes were assumed to locate in the esophagus.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the mean number of weakly acidic reflux episodes were determined at double the rate of the mean number of acidic reflux episodes, which was statistically significant (p<0.01). In a recent study, Liu et al 26 showed that MII-pH monitoring detected a 3-fold increase in nonacid reflux episodes in comparison with acid reflux episodes. The impact of non-acid reflux is very important in a study population such as the one in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal pH-monitoring is one of the most convenient methods but it only recognizes acidic episodes of reflux 12,13,23,24 . A significant proportion of reflux episodes are known to be non-acidic, especially in infants [23][24][25][26][27] . As emphasized in the most recent guidelines, combined multiple intraluminal impedance and pH monitoring (MII-pH) is the most reliable method to evaluate GER 5,10 .…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that weakly acidic reflux may play a role in the pathogenesis of reflux esophagitis (14). Study by Liu et al found that the best predictors of reflux esophagitis are DeMeester score ≥ 21 and the duration of the longest acid reflux ≥ 17 minutes, as well as the occurrence of acid reflux over 5 minutes (36). These results indicate that macroscopic changes of esophageal mucosa are more common in patients with increased exposure to acid, as previously reported in adult studies (52).…”
Section: The Role Of Ph-mii Parameters In Prediction Of Reflux Esophamentioning
confidence: 93%
“…Endoscopy is a highly specific (90-95%) method for diagnosing of GERB (14,36,37). The sensitivity of endoscopy is low and does not exceed 50% in different studies (referent test pH-MII monitoring) (14,25,38).…”
Section: Combined Ph-mii Monitoring: Advantages and Disadvantagesmentioning
confidence: 99%